Increasing traceability of halal medicine consumption through integrated data mining and digital payment in Indonesia: an approach - Haq, Avip Zain; Cotama, Cahana Rastra (Journal of Halal Product and Research, 2025)
Indonesia is a country with a Muslim population of 249,82 million (87.2%) in 2023. The potential of this large Muslim population is believed to drive a great demand for halal products. Based on the results of a national-scale drug update survey in Indonesia in 2019, the total number of drugs circulating in 34 provinces was 97,759 drug items, with data on the number of drugs registered in the Food and Drug Supervisory Agency (BPOM) registration of 14,263 drug items, due to the condition of the Indonesian pharmaceutical market, which is worth around USD 10.11 billion in 2021 and is estimated to reach USD 27 billion or more in 2035. This study aimed to develop an integrated data mining model that involves actors in the medical services sector and their digitalization systems, to improve downstream tracking of halal drug consumption. More than 50 articles were collected and analysed to create an integrated data mining model approach. This economic digitalization of digital payment can be the key to increasing traceability of halal drug consumption in Indonesia. The collected transaction data model contains halal-certified and non-halal medicines along with transaction details. Combined with data collection from various sources, such as medical records and BPJS data, it can complete the overall tracing of drug consumption on the downstream side. The results of this data integration can be measured and become an evaluation of drug consumption patterns in health facilities for patients   Keywords: Traceability, Halal Medicine, Data Mining, Digital Payment